Compte-rendu de « Black Dolls, la collection Deborah Neff » - Emmanuel Falguières (Transatlantica)
From February 23rd to May 20th 2018, the Parisian exhibition space La maison rouge presents for the first time outside of the United States Deborah Neff private collection of black dolls.